Modal Birefringence: Tunable Modal Birefringence in a Low‐Loss Van Der Waals Waveguide (Adv. Mater. 27/2019). Issue 27 (2nd July 2019) - Hu, Debo; Chen, Ke; Chen, Xinzhong; Guo, Xiangdong; Liu, Mengkun; Dai, Qing
Abstract : In article number1807788, Mengkun Liu, Qing Dai, and co‐workers use a metal‐coated atomic force microscope tip with a beam of near‐infrared light focused on its apex to launch and image the orthogonally polarized ordinary and extraordinary waveguide modes propagating in MoS2 . In a MoS2 crystal with a suitable thickness, the ordinary and extraordinary modes can be degenerate in momentum space and propagate with the same phase velocity in real space.